Research on the Parameters of Gasoline Engine Injectors - Brunius, Giedrius; Sabaliauskas, Arturas (Jaunųjų mokslininkų darbai, 2021)
Automotive engines are getting more and more advanced. This causes the change in the development of injectors. The nozzle spray fuel quality has to meet certain requirements, such as sprayed droplet size, flare length, and sprayed fuel. Using the method of analysis and synthesis of scientific literature sources, the main parameters of gasoline injectors were calculated in this work. The results of the research have been compared with calculated parameters obtained from the injectors test stand. The paper has been prepared on the basis of G. Brunius’ Master Thesis.